Boswellia Essential Oil: Natural Antioxidant as an Effective Antimicrobial and Anti-Inflammatory Agent - Diana Obiștioiu; Anca Hulea; Ileana Cocan; Ersilia Alexa; Monica Negrea; Iuliana Popescu; Viorel Herman; Ilinca Merima Imbrea; Gabriel Heghedus-Mindru; Mukhtar Adeiza Suleiman; Isidora Radulov; Florin Imbrea (MDPI AG, 2023)
The research aimed to determine the chemical composition, the antioxidant and anti-inflammatory activity as well as the antimicrobial activity against Gram-positive, Gram-negative and two fungal Candida ATCC strains of a commercial Boswellia essential oil (BEO) containing Boswellia carteri, Boswellia sacra, Boswellia papryfera, and Boswellia frereana. Additionally, molecular docking was carried out to show the molecular dynamics of the compounds identified from the essential oil against three bacterial protein targets and one fungal protein target. The major components identified by GC-MS (Gas Chromatography-Mass Spectrometry) were represented by α-pinene, followed by limonene. Evaluation of antioxidant activity using the DPPH (2,2-Diphenyl-1-Picrylhydrazyl) method showed high inhibition comparable to the synthetic antioxidant used as a control. Oxidative stability evaluation showed that BEO has the potential to inhibit primary and secondary oxidation products with almost the same efficacy as butylated hydroxyanisole (BHA). The use of BEO at a concentration of 500 ppm provided the best protection against secondary oxidation during 30 days of storage at room temperature, which was also evident in the peroxide value. Regarding the in vitro anti-inflammatory activity, the membrane lysis assay and the protein denaturation test revealed that even if the value of protection was lower than the value registered in the case of dexamethasone, the recommendation of using BEO as a protective agent stands, considering the lower side effects. Gram-positive bacteria proved more sensitive, while Pseudomonas aeruginosa presented different sensitivity, with higher MICs (minimal inhibitory concentration). Haemophilus influenzae demonstrated a MIC at 2% but with consecutive inhibitory values in a negative correlation with the increase in concentration, in contrast to E. coli, which demonstrated low inhibitory rates at high concentrations of BEO. The computational tools employed revealed interesting binding energies with compounds having low abundance. The interaction of these compounds and the proteins (tyrosyl-tRNA synthetase, DNA gyrase, peptide deformylase, 1,3-β-glucan synthase) predicts hydrogen bonds with amino acid residues, which are reported in the active sites of the proteins. Even so, compounds with low abundance in BEO could render the desired bioactive properties to the overall function of the oil sustained by physical factors such as storage and temperature. Interestingly, the findings from this study demonstrated the antioxidant and antimicrobial potential of Boswellia essential oil against food-related pathogens, thus making the oil a good candidate for usage in food, feed or food-safety-related products.